Basic design procedure for an internally geared screw compressor. Issue 1 (September 2021) - Read, Matthew
Abstract: The internally geared gerotor type of positive displacement machine is widely used for pumping applications, but can also be used to achieve internal compression or expansion of a working fluid. A further development of this configuration is the application of helical twist to the inner and outer rotors. Previous studies have shown that this can decrease the power transferred between rotors, and increase the relative maximum flow areas at the inlet and discharge ports. There are possible benefits to this configuration when compared to conventional twin-screw machines, including reduced leakage area, stiffer rotors, and co-directional thermal expansion of rotors. However, no experimental data is currently available for this configuration, and optimising the geometry of the gerotor screw machine requires a detailed understanding of the porting, leakage flows and mechanical losses. An experimental programme is being conducted to investigate the influence of these factors on performance. This paper discusses preliminary results from geometrical analysis leading to a simple design procedure. The basic design of an internally geared air compressor is demonstrated, based on the operation characteristics of a conventional twin screw machine.